Role of the cytoskeleton in cellular reprogramming: effects of biophysical and biochemical factors - Ekaterina Momotyuk; Nour Ebrahim; Ksenia Shakirova; Erdem Dashinimaev (Frontiers in Molecular Biosciences, 2025)
The cytoskeleton plays a crucial role in regulating cellular behavior, acting as both a structural framework and a mediator of mechanical and biochemical signals that influence cell fate. In the context of cellular reprogramming, modifications to the cytoskeleton can have profound effects on lineage commitment and differentiation efficiency. This review explores the impact of mechanical forces such as substrate stiffness, topography, extracellular fluid viscosity, and cell seeding density on cytoskeletal organization and mechanotransduction pathways, including Rho/ROCK and YAP/TAZ signaling. Additionally, we examine the influence of biochemical agents that modulate cytoskeletal dynamics, such as actin and microtubule polymerization inhibitors, and their effects on stem cell differentiation. By understanding how cytoskeletal remodeling governs cellular identity, this review highlights potential strategies for improving reprogramming efficiency and directing cell fate by manipulating mechanical and biochemical cues.